Frailty and Mortality in Kidney Transplant Recipients - McAdams-DeMarco, M. A. (Am J Transplant, 2014)
We have previously described strong associations between frailty, a measure of physiologic reserve initially described and validated in geriatrics, and early hospital readmission as well as delayed graft function. The goal of this study was to estimate its association with postkidney transplantation (post-KT) mortality. Frailty was prospectively measured in 537 KT recipients at the time of transplantation between November 2008 and August 2013. Cox proportional hazards models were adjusted for confounders using a novel approach to substantially improve model efficiency and generalizability in single-center studies. We precisely estimated the confounder coefficients using the large sample size of the Scientific Registry of Transplantation Recipients (n = 37 858) and introduced these into the single-center model, which then estimated the adjusted frailty coefficient. At 5 years, the survivals were 91.5%, 86.0% and 77.5% for nonfrail, intermediately frail and frail KT recipients, respectively. Frailty was independently associated with a 2.17-fold (95% CI: 1.01–4.65, p = 0.047) higher risk of death. In conclusion, regardless of age, frailty is a strong, independent risk factor for post-KT mortality, even after carefully adjusting for many confounders using a novel, efficient statistical approach.